FINANCIAL REPORT ANALYSIS: FROM DATA TO VALUABLE INFORMATION (CASE STUDY OF A WORKSHOP SERVICE BUSINESS) - Rita J D Atarwaman; Nadia Indra; Bayu Muhaimin; Nurfira Tuharea; Refial Fadhil Marasabessy; Dean Marchia Unawekla; Ina Belay; Fakhri Azmi Syahbani; Fahratun Rizky Lisaholith; Adha Sahar Pradella; Debora Evanya Sinaga; Putri Maharani Ratuloly; Fensya Penina Tosil; Ardhansyah Iwan Putra; Gusti Tuara (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the financial statements of an automotive repair service business in order to transform financial data into useful information for decision-making. The method used is descriptive analysis of the balance sheet, income statement, and statement of changes in equity prepared by the workshop business entity. The results show that the workshop business has a healthy financial position with adequate current and fixed assets, as well as a positive net profit. The conclusion of this study is that financial statements provide essential information for management in planning and controlling the business.